Multisensory training based on an APP for enhanced verbal working memory in older adults - Rongjuan Zhu; Xiaoliang Ma; Ziyu Wang; Qi Hui; Xuan Wang; Xuqun You (Internet Interventions)
With the increasing aging population, contemporary society faces the imperative to develop approaches that efficiently delay the age-related decline in working memory capacity, which is a critical area within cognitive aging research. Nevertheless, there is insufficient evidence to support the efficacy of verbal working memory training across various sensory modalities (visual, auditory, and audiovisual) in enhancing the verbal working memory capacity of older adults. In this study, 60 healthy older adults (mean age = 67.07 ± 3.79 years, comprising 34 women and 26 men, mean education = 15.55 ± 2.53 years) were randomly assigned to one of four groups: visual verbal working memory (V-VWM) group, auditory verbal working memory (A-VWM) group, visual-auditory verbal working memory (VA-VWM) group, and a control group. The training duration spanned 12 days. We also investigated whether baseline level and education predicted the outcomes. Findings indicated that V-VWM training had a large effect on improving V-VWM task performance (Cohen's d = 1.765), A-VWM training showed a substantial effect on A-VWM task performance (Cohen's d = 1.904), and VA-VWM training demonstrated a significant effect on VA-VWM task performance (Cohen's d = 2.319) over pretest scores in older adults. Enhancements achieved through V-VWM training exhibited near transfer effects, improving performance in both A-VWM and VA-VWM tasks. In contrast, gains from A-VWM training were selectively transferred to the VA-VWM task. Furthermore, VA-VWM training led to improvements not only in V-VWM and A-VWM tasks but also extended to verbal operation span task with a significant 29.7 % increase. However, no significant transfer effects were observed for the DSF and DSB tasks across the three training groups. The maintenance effect of VA-VWM training persisted for two weeks across tasks involving VA-VWM, V-VWM, and A-VWM. The baseline of VWM span score influence the effect of V-VWM training and transfer effect of VA-VWM training. Education level did not predict the training effects of V-VWM, A-VWM, and VA-VWM. These findings highlight the nuanced effects of sensory-specific verbal working memory training in older adults, emphasizing the potential of tailored interventions to enhance specific aspects of cognitive function, while also highlighting the promising applications of mobile device training in enhancing cognitive skills among the elderly.